Вивчення протимікробної активності 4-(R-іліденаміно)-3-(морфолінометилен)-4Н-1,2,4-триазол-5-тіолів - Щербина, Роман Олександрович; Панасенко, Олександр Іванович; Книш, Євгеній Григорович; Камишний, Олександр Михайлович; Shcherbyna, R. О.; Panasenko, O. I.; Knysh, Ye. H.; Kamyshnyy, O. M. (My University, 2015)
За даними Всесвітньої організації охорони здоров’я (ВООЗ) летальні випадки, спричинені патогенними мікроорганізмами, займають одне з провідних місць. Особливо гостро ця проблема постає в країнах, де економічні можливості не дають змоги утримувати спалахи інфекційних захворювань під повним контролем [1]. Тому необхідність в нових, доступних та високоактивних бактерицидних препаратах є доцільною та обґрунтованою [2]. Метою нашої роботи є вивчення протимікробних та протигрибкових властивостей 4-(R-іліденаміно)-3-(морфолінометилен)-4H-1,2,4-триазол-5-тіолів методом серійних розведень та встановлення деяких закономірностей залежності «структура–дія». According to the information of the World Health Organization (WHO) the lethal cases caused by pathogenic microorganisms occupied the one of the leading places. Most acutely the problem posed in countries where economic opportunities does not hold the flashes of infectious diseases under control. Therefore necessity of the new, available and high bactericidal drugs is reasonable and justified. Unfortunately, in literary sources missing information which devoted to 4-(R-ylidenamino)-3-(morpholinomethylene)-4H-1,2,4-triazole-5-thioles. The main aim of our work are studying antimicrobial and antifungal properties of 4-(R-ylidenamino)- 3-(morpholinomethylene)-4H-1,2,4-triazole-5-thioles by serial dilutions method and establishing some patterns dependence “structure-action”. The research was conducted by using of standard test cultures: Staphylococcus aureus, Escherichia coli, Pseudomоnas aeruginosa, Candida albicans. The trimethoprimum was used as reference preparation for antimicrobial activity studying, the nystatinum – for antifungal.
The studing of antimicrobial activity of 4-(R-ylidenamino)-3-( morpholinomethylene)-4h-1,2,4-triazole-5-thiol
Keywords: 1,2,4-триазол; протимікробна активність; метод серійних розведень; 1,2,4-triazole; antimicrobial activity; the method of serial dilutions